2012
DOI: 10.1055/s-0032-1304275
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Quality of Life in Limb Amputees

Abstract: In the United States, there are $1.7 million individuals living with limb loss. 1 One in 190 Americans currently live with the loss of limb and this number is estimated to double by the year 2050. 1 Data collected by the National Limb Loss Information Center (2008) reported that the rates of trauma-and cancer-related amputations have declined although the number of amputations related to vascular disease has increased. 2 Limb amputation is a life-changing event that signifies long-term physical, social, psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
2
12
0
3
Order By: Relevance
“…In fact, a coping strategy focused on self-distraction may minimize pain sensitivity (van der Hulst, Vollenbroek-Utten, Schreurs, Rietman & Hermens, 2010), and reduce physical and psychological suffering (Desmond & MacLachlan, 2006a) associated with pain, while the active coping strategies are more beneficial in solving problems and helping the individual to resume their daily activities (Livneh et al, 1999). Religion and spirituality have been studied in this population with positive results, not only regarding satisfaction with life, but also general health and social integration (Peirano & Franz, 2012) and this study is in accordance with these results.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, a coping strategy focused on self-distraction may minimize pain sensitivity (van der Hulst, Vollenbroek-Utten, Schreurs, Rietman & Hermens, 2010), and reduce physical and psychological suffering (Desmond & MacLachlan, 2006a) associated with pain, while the active coping strategies are more beneficial in solving problems and helping the individual to resume their daily activities (Livneh et al, 1999). Religion and spirituality have been studied in this population with positive results, not only regarding satisfaction with life, but also general health and social integration (Peirano & Franz, 2012) and this study is in accordance with these results.…”
Section: Discussionsupporting
confidence: 88%
“…One reason could be the differences in the background and demographics of the participants in this study and those in the study by Holzer et al (2014). However, the study conducted by Peirano & Franz (2012) uncovered results similar to this study, where "existential spirituality, female gender, and age above 50 years related to higher QOL in clients with a history of limb amputation". They found that male amputees were comparable to female amputees, indicating that they had poorer quality of life in terms of physical and health aspects.…”
Section: Quality Of Lifesupporting
confidence: 54%
“…The positive role of spirituality has been recently highlighted for the female gender in particular [25]. Levels of anxiety and depression have been extensively studied, being significantly higher than in the general population and also influencing quality of life [26,27].…”
Section: Resultsmentioning
confidence: 99%